Construction of an integrated treatment and management model for psychiatric emergency and intensive care units in a specialized psychiatric hospital: practice of subspecialty development - Wang, Yi-chao; Yu, Hui; Luo, Fu-gang; Wang, Hong-mei (Frontiers in Health Services, 2025)
BackgroundPsychiatric patients admitted through emergency pathways often presented with severe comorbid physical illnesses, which posed challenges for timely diagnosis and effective management in psychiatric specialty hospitals. To address this gap, our hospital established an integrated model that linked the Psychiatric Emergency Department (PED) with the Psychiatric Intensive Care Unit (PICU), aiming to create a continuous and coordinated emergency–critical care system.Description of the modelThe PED–PICU integrated model was developed through progressive institutional innovations, including the establishment of a dedicated PICU, functional integration of the PED, and the creation of specialized rapid-response centers. This model enabled early identification of critical conditions, seamless transfer between emergency and intensive care, and continuity of treatment until recovery.Experience and outcomesIn practice, the model improved coordination between emergency and critical care teams, facilitated timely interventions, and ensured that patients with severe psychiatric and medical comorbidities received comprehensive management within a single institutional framework. The integration also strengthened multidisciplinary collaboration and highlighted the unique role of psychiatric specialty hospitals in managing complex emergencies.ConclusionsThe PED–PICU integrated model represented a pioneering and unique practice in psychiatric specialty hospitals. By closing the gaps between emergency stabilization and intensive care, it established a closed-loop system that might serve as a valuable reference for developing similar subspecialties and improving emergency–critical care pathways in mental health services.